2007
DOI: 10.1207/s15327663jcp1701_9
|View full text |Cite
|
Sign up to set email alerts
|

Deliberative and Automatic Bases of Suspicion: Empirical Evidence of the Sinister Attribution Error

Abstract: This research explores perceptions of interpersonal influence in the form of flattery that occurs in a consumer retail setting. Across 4 experiments, results demonstrate empirical evidence of a sinister attribution error (Kramer, 1994), as consumer reactions to flattery were more negative than warranted by the situation. Results across 3 experiments demonstrated that there are 2 types of information processing occurring when consumers make trust judgments in response to flattery. Depending on when flattery occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(167 citation statements)
references
References 51 publications
8
151
2
6
Order By: Relevance
“…Past research has suggested that perceivers use communication speed as a positive heuristic cue for the intelligence of the speaker, such that they tend to infer that fast speakers are intelligent (Smith and Shaffer 1995). The present findings show that in the context of advertising disclaimers for untrusted brands, perceivers also use fast speech as a negative heuristic cue for the trustworthiness of the advertiser, supporting research suggesting that consumers are vigilant for information that might convey ulterior motives on the part of advertisers (Main et al 2007). One explanation for the divergent effects of communication speed in Smith and Shaffer's (1995) studies versus in our own is that the abrupt change of pace between the main advertisement and the end-of-advertisement disclaimer might draw consumer attention and raise suspicion.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Past research has suggested that perceivers use communication speed as a positive heuristic cue for the intelligence of the speaker, such that they tend to infer that fast speakers are intelligent (Smith and Shaffer 1995). The present findings show that in the context of advertising disclaimers for untrusted brands, perceivers also use fast speech as a negative heuristic cue for the trustworthiness of the advertiser, supporting research suggesting that consumers are vigilant for information that might convey ulterior motives on the part of advertisers (Main et al 2007). One explanation for the divergent effects of communication speed in Smith and Shaffer's (1995) studies versus in our own is that the abrupt change of pace between the main advertisement and the end-of-advertisement disclaimer might draw consumer attention and raise suspicion.…”
Section: Discussionsupporting
confidence: 78%
“…We suggest that consumers may believe that fast disclaimers represent a tactic used by advertisers to hide information or to deceive consumers. Just as ingratiation and flattery tactics can serve as cues for the lack of trustworthiness in salespersons (Campbell 1995;Main, Dahl, and Darke 2007), we suggest that fast disclaimers can serve as cues for the lack of trustworthiness in advertisements.…”
Section: Advertisement Disclaimers and Speed Of Communicationmentioning
confidence: 87%
“…While the current research utilized undergraduate business students as participant consumers, in the domain of interest, students have experience in the marketplace making similar decisions after being exposed to information in the environment. Also, the use of undergraduates to explore issues of trust and consumer behaviors is not unusual in the literature (Erdem and Swait, 2004;Main et al, 2007). Further, although the effect of demographic variables as moderators of processes related to perceptions of unethical behavior remains an empirical question, there is ample reason to believe that older and more experienced consumers may have an exaggerated compulsion seek out information on unethical agents.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Moreover, these kinds of recommendations provide an excellent background for studying trustworthiness, because it is unclear whether these recommendations are based on true enthusiasm towards a product, or on the desire for financial gain. The ambiguity of this financially motivated behavior creates some level of suspicion and distrust (Main, Dahl, & Darke, 2007), and fosters the use of facial cues to evaluate the other person (see Hassin & Trope, 2000).…”
Section: Relationships and Facial Cuesmentioning
confidence: 99%